Analisis Pengungkapan Triple Bottom Linedan Faktor yang Mempengaruhi; Lintas Negara Indonesia dan Jepang - Z, Sandra Aulia; Kartawijaya, Tb. Mh. Idris (UI Scholars Hub, 2013)
Current firm performance is not only measured by economic term (single bottom line) but also by social and environmental (triple bottom line). Purposes of this research are analyzing of TBL disclosure and influences factors, by using sample of companies in Indonesia and Japan. This paper investigates Triple Bottom Line (TBL) disclosure of 50 of the largest Indonesian and Japanese companies by using secondary data. Twenty two disclosure criteria were developed for each of the TBL disclosure areas: economic, social, and enviromental. Disclosure information was examined in annual reports, separate or stand-alone report and company‟s website. Regression analysis has been used to examine the determinants of TBL disclosure practice empirically. Our result indicated that, for total of TBL disclosure (combining economic, social and environmental catagories), the extent of reporting is higher for firm with larger size and higher liquidity, and special for environmental disclosure for firm with membership in the manufacturing industry for Indonesian companies. Futher analysis indicated that the results of the total TBL disclosure are primarily driven by non-economic disclosures. We also found that the extent of overall TBL disclosure is higher for Japanese firms, with environmental disclosure being the main key. This result could be attributed to the different national cultures and to the regulation environment between Indonesian and Japan.